Plants from Arid Zones of Mexico: Bioactive Compounds and Potential Use for Food Production - Isabel Márquez-Rangel; Mario Cruz; Alberto A. Neira-Vielma; Sonia N. Ramírez-Barrón; Pedro Aguilar-Zarate; Ruth Belmares (Resources)
(1) Background: Climate change has several consequences; one of them is increasing the severity of droughts. This has led to an opportunity to study arid zone plants as food sources that have potential biological activities and improve consumer health. (2) Methods: In this work, we review recent research focused on the traditional use and importance of arid zone plants, their nutritional contribution, and their beneficial effects on health when they are consumed; these effects are primarily because of their antioxidant activity, which inhibits free radicals and contributes to improved nutrition and benefits consumer health. (3) Results: Several plant-based functional food studies have shown that the consumption of bioactive compounds is a complement to drugs for preventing some chronic degenerative diseases, such as gastrointestinal diseases, diabetes, and obesity. (4) Conclusions: Given all of the previously mentioned factors, plants from arid zones are potential sources for obtaining bioactive compounds with low water requirements.